Arthur Cimwanga Badibanga 2016. Mbororo, invasion of a nation. Review - Taluah, Reginald Asangba (AAeO - Afrikanistik-Aegyptologie-Online, 2018)
Mbororo, Invasion of a Nation by Arthur Cimwanga Badibanga published by Lambert Academic Publishing, Saarbruecken, 2016 is predominantly a drama interspersed with folk song and a bit of poetry. Other notable plays by Badibanga include La Derision Autoritaire (1993) and L’Innocence sans Preuve (1992). The impacts of nomadic tribes like the Mbororo in their migrations and settlements in most parts of the sub-Saharan Africa have been of great concern to most governments. Mindful of these instances, the playwright attempts to unravel the causes for such conflicts between the indigenes and the nomadic tribes and their subsequent search for freedom to live according to the respective traditions. The play is set in three acts and revolves around the Mbororo and key figures in Congolese society and the world at large. The concerns raised in the play are vital to these very recent times as these are the prevailing issues. What is most significant to this play is that fact that he provides a clear resolution to conflicts at stake. Notwithstanding the significance of the themes that Badibanga chooses to tackle, the play is over ambitiously populated with diverse characters and entities such Church members, Human Rights Watch, Red Cross, United Nations, African Union who supposedly appear in passing and carry individual voices. A limited number of character can echo the sentiments and thoughts expressed therein and would have given the play a more unified plot. There are some particular issues with the typesetting as sentences and sometimes words are separated by unnecessary gaps. Being a translation of the French original text (Cimwanga 2016), readers would have also expected that the Abstract to the book to be in English like all other translations.More so, there exist some typos and grammatical incoherencies in the writing, most of which could have been corrected with the appropriate attention. For instance, quite apart from Act One, which is rendered appropriately, Act Two and Act Three have a misspelt "Act" as "Acte". Interestingly so, the common idiom ‘A stitch in time saves nine’ is rendered as ‘… a stick in time saves nine’ as conveyed by Bakumbasasa in Act three (31). The play is overall a good attempt to address the issues of freedom and conflict pertain in some parts of Africa and the Congo in particular. However, the ingredients that are crucial for the success of a play are not best employed by the playwright in this regard.